Associação de extratos naturais à fotobiomodulação no tratamento do envelhecimento cutâneo: estudo in vitro - Machado, Gabriela Benedito (2019)
The alterations that arise as a result of photoaging are attributed to the continuous generation of reactive oxygen species (ROS) by ultraviolet radiation, which cause tissue injury due to the high reactivity with biomolecules, mainly Lipids, proteins and DNA. Plant extracts contain several components that have antioxidant properties and can be used for the treatment of photoaging by reducing the concentration of ROS in the tissue. The Photobiomodulation (PBM) is a treatment based on the action exerted by light on tissues, resulting in bioenergetic, bioelectric and biochemical modifications that culminate in the modulation of several cellular functions. The objective of this work was to evaluate the effect of PBM with red LED light associated with natural extracts with different polyphenolic contents in normal human keratinocytes submitted to UVA radiation. The extracts of chamomile and fig, FBM 640±12.5 nm (1 J/cm2) and UVA 366±10 nm (9 J/cm2) were evaluated. The UVA radiation caused a reduction in cell viability, and the association of extract 0.3% with FBM was not able to regain viability. The combined treatment was repeated using the extracts of chamomile and fig 0.05%, thus precisely because there was no effective improvement of the viability by the Association of Therapies, it was decided to understand the effects of the treatments, evaluating the Expression of mRNA antioxidant enzymes (catalase) and DNA repair genes associated with different repair mechanisms (ERCC2, ERCC1, OGG1, BRCA1, DBB1 and TP53). The UVA radiation reduced the expression of catalase and increased the expression of OGG1, BRCA1e TP53, without presenting alterations in DBB1, ERCC1 and ERCC2 showing that there was activation of the mechanisms of DNA repair, especially the mechanism of repair by excision of bases and Homologous recombination. The combined use of the extracts with FBM altered differently the evaluated genes, and the fig extract had a protective effect reaching levels of mRNA expression of the various genes larger than the group exposed to UVA